Determing OHI-S and DMFT in students at Universidad Veracruzana, México - Gómez Ríos, Norma Inés; Morales García, Manuel Higinio (Revista Chilena de Salud Pública, 2012)
Introduction: Knowledge of the dental health of the population constitutes a fundamental task of public health, since oral diseases- such as cavities and periodontal disease- are the health conditions with highest incidence and prevalence around the world. The objective of this study was to determine the index of decayed, missing or filled teeth (DMFT) and the simplified oral health index (OHI-S) of first year university students in the state of Veracruz, province of Mexico. Material y method: A descriptive, cross-sectional, observational study was carried out, applying a comprehensive health exam which consisted of two parts: a questionnaire and a clinical exam. Results: The DMFT index was 13.1. The prevalence of cavities was 80.9, missing teeth was 37.9 y filled teeth was 47.0. The OHI-S was the following: 81.5%